Analysis of Scientific Field Suitability and the Goal Achievement of Certified Independent Study Internship and Learning Activity Form for Undergraduate Students of Social Science Education at Universitas Negeri Malang - David Golddra Pamungkas Bramantya; Neni Wahyuningtyas (Laboratorium Program Studi Pendidikan Guru Sekolah Dasar FKIP Universitas Riau, 2023)
Form of Learning Activity (BKP) of certified independent study internship (MSIB) is an activity that is intended for students to get to know the current world of work. However, based on its implementation, the achievement of the objectives and suitability of BKP MSIB with the scientific field study programs becomes a real issue in the implementation of BKP MSIB. This paper aims to describe the achievement of the objectives of BKP MSIB for undergraduate students at the Social Science Education Study Program of UM, as well as the suitability of BKP MSIB followed by undergraduate students at the UM Social Science Education with the scientific field study program. The study uses a descriptive narrative study method to answer the formulation of the problem based on the students’ experience of BKP MSIB participants who came from S1 UM Social Science Education. The research results indicate the achievement of the objectives of BKP MSIB. Students get the right fulfillment to obtain experience in the implementation of BKP MSIB. The right fulfillment to obtain experience is evidenced by the experience of getting off the field for 1-4 months (for certified internships), as well as the real-world issues, which are raised to be reviewed in the classroom (for Certified Independent Studies). Based on its implementation on undergraduate students of UM Social Science Education, it turns out that BKP MSIB still has shortcomings. The shortcomings include the incompatibility between BKP MSIB taken by S1 students of UM Social Science Education with the scientific field study program. Furthermore, based on the research, it is still found students who have a sense of “compulsion” to undergo BKP MSIB MBKM.